Identification of the microglia-associated signature in experimental autoimmune encephalomyelitis - Wu, Yan; Wang, Jianhong; Chen, Bo; Guo, Yuxue; Gan, Ping; Han, Yanbing (Frontiers in Immunology, 2025)
BackgroundMultiple sclerosis (MS) is a chronic neuroinflammatory disorder characterized by demyelination and immune dysregulation, and microglia play a central role in disease progression. Despite this, the specific microglial gene signatures contributing to MS remain inadequately characterized.MethodsWe utilized an experimental autoimmune encephalomyelitis (EAE) mouse model and performed RNA sequencing to identify differentially expressed Messenger RNAs (DEmRNAs), Long Non-Coding RNAs (DElncRNAs), Circular RNAs (DEcircRNAs), and microRNAs (DEmiRNAs) in microglia. A machine learning approach incorporating five distinct algorithms was applied to select a robust multigene signature. The biological functions of the included genes were assessed through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses and validated by quantitative reverse transcription PCR (qRT-PCR). Additionally, molecular docking studies were conducted to explore potential interactions with approved MS therapeutics.ResultsSix DEmRNAs were identified as key microglia-associated biomarkers: Neutrophilic Granule Protein (NGP), Histone Cluster 1 H2B Family Member J (HIST1H2BJ), Phenazine Biosynthesis-Like Domain-Containing Protein 1 (PBLD1), Muscleblind-Like Protein 3 (MBNL3), Lymphocyte Antigen 180 (CD180), and Coagulation Factor X (F10). All six genes were found to be upregulated in EAE microglia compared to phosphate-buffered saline (PBS) treated mice. These genes are primarily involved in immune-related pathways, including Toll-like receptor (TLR) signaling, and interact with MS therapeutics such as teriflunomide. Among the identified DEcircRNAs, circGAS2 (mmu-circ-0001569) was significantly upregulated, suggesting its potential regulatory role in microglial function. The expression trends of these biomarkers were validated via quantitative reverse transcription PCR (qRT-PCR) and Western blot analysis.ConclusionsThis study provides a comprehensive microglial gene signature for EAE, highlighting the involvement of TLR pathways and circRNA-mediated regulation in MS pathogenesis. These findings provide a foundation for future research into microglia-targeted therapies and diagnostic tools for MS.